Born to love you - Martin, Coco; Quinto, Angeline; Tantay, Al; De Guzman, Malou; Santos-Consio, Charo; Santos, Malou; Nacianceno, Rodel P. (2012)
Coco and Angeline play Rex and Joey respectively. Rex is a photographer who struggled his way just to survive. He comes from a broken family and practically grew up his lonesome. Joey is a tourist guide in search for her true father. She comes from a poor family who also struggles with the day to day realities of life. "born to love you" is more than just a love story of the two lead characters who affect each other's lives as they fell in love but it also celebrates the beauty of life, love, relationships and existence.